Phytochemical Profiling of Ethanol Extract from Cocoa Leaves (Theobroma Cacao L.) using Gas Chromatography-Mass Spectrometry - Savira, Nadyatul Ilma Indah; Nurfadhilah , Findiyas Azizah; Hariani, Sulifah Aprilya; Maulana, Alfan Irsyad; Wulandari, Amalia (LenteraBio : Berkala Ilmiah Biologi, 2024)
Cocoa (Theobroma cacao L.) is one of the highest plantation commodity crops in Indonesia. Previous research showed that cocoa leaves were used as a larvicide, antioxidant, antibacterial, and anticancer. This study aims to determine the phytochemical compounds of ethanol extract of cocoa leaves qualitatively and quantitatively. Extraction of cocoa leaves using maceration method and phytochemical screening using Gas Chromatography-Mass Spectrometry (GC-MS) method. Based on the qualitative phytochemical screening of this study, alkaloid, flavonoid, and saponin tests showed positive results. GC-MS test analysis results showed ethanol extract from cocoa leaves detected 20 compounds. The extract with ethanol solvent produced the most compounds namely glycerol 1,2,3-Propanetriol, 1-acetate (CAS) 1-Acetoxy-2,3-Dihydroxypropane; 1,2,3-Propanetriol, monoacetate; and 1,2,3-Propanetriol, triacetate, phenolic 1,4-Benzenediol (CAS) Hydroquinone, and alkaloid 1H-Indole (CAS) Indole. Therefore, cocoa leaves have many bioactive compounds that have potent pharmacological effects.